The Masyumi Legacy: Between Islamist Idealism and Political Exigency - Fealy, Greg; Platzdasch, Bernhard (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
Masyumi's name and symbol have an enduring appeal, particulary to modernist Muslims. Althougt the party was disbanded in 1960, Muslims intellectuals, activitis and politiciants continue to invoke its name and identify themselves as being part of the Masyumi heritage. For example, no less than four parties at the 1999 general elections used symbols based on Masyumi's bulan bintang (crecent moon and star) logo and they jostled among themselves for recognation as the party most representative of Masyumi values and tradition. Many of these modernist felt bound by an associative spirit to the masyumi 'family', which was commonly referred to as the Keluarga Bulan Bintang (Crescent Moon and Star Family).DOI: 10.15408/sdi.v12i1.646